Molecular and pathologic insights from latent HIV-1 infection in the human brain - Desplats, Paula (Lippincott Williams & Wilkins, 2013)
OBJECTIVE: We aimed to investigate whether HIV latency in the CNS might have adverse molecular, pathologic, and clinical consequences. METHODS: This was a case-control comparison of HIV-1 seropositive (HIV+) patients with clinical and neuropathologic examination. Based on the levels of HIV-1 DNA, RNA, and p24 in the brain, cases were classified as controls, latent HIV CNS infection, and HIV encephalitis (HIVE). Analysis of epigenetic markers including BCL11B, neurodegeneration, and neuroinflammation was performed utilizing immunoblot, confocal microscopy, immunochemistry/image analysis, and qPCR. Detailed antemortem neurocognitive data were available for 23 out of the 32 cases. RESULTS: HIV+ controls (n = 12) had no detectable HIV-1 DNA, RNA, or p24 in the CNS; latent HIV+ cases (n = 10) showed high levels of HIV-1 DNA but no HIV RNA or p24; and HIVE cases (n = 10) had high levels of HIV-1 DNA, RNA, and p24. Compared to HIV+ controls, the HIV+ latent cases displayed moderate cognitive impairment with neurodegenerative and neuroinflammatory alterations, although to a lesser extent than HIVE cases. Remarkably, HIV+ latent cases showed higher levels of BCL11B and other chromatin modifiers involved in silencing. Increased BCL11B was associated with deregulation of proinflammatory genes like interleukin-6, tumor necrosis factor–α, and CD74. CONCLUSION: Persistence of latent HIV-1 infection in the CNS was associated with increased levels of chromatin modifiers, including BCL11B. Alteration of these epigenetic factors might result in abnormal transcriptomes, leading to inflammation, neurodegeneration, and neurocognitive impairment. BCL11B and other epigenetic factors involved in silencing might represent potential targets for HIV-1 involvement of the CNS.